Soluble endothelial protein C receptor (sEPCR) as an inflammatory biomarker in naive HIV-infected patients during ART. (16th February 2016) - Chiappetta, S.; Ripa, M.; Galli, L.; Razzari, C.; Longo, V.; Galli, A.; Faioni, E. M.; Nozza, S.; Lazzarin, A.; Tambussi, G.
Abstract: Background: After the advent of ART, non-AIDS-related comorbidities are the main causes of death in HIV patients. Multiple biomarkers have been studied as markers of disease. We wanted to test soluble endothelial protein C receptor (sEPCR) in an HIV setting. Objectives: The primary objective was to determine whether sEPCR decreases after 48 weeks of ART in naive HIV patients. Secondary objectives were to compare sEPCR levels between patients with chronic HIV infection (CHI) and primary HIV infection (PHI) and to analyse if there is a correlation between sEPCR and both immunovirological parameters and different markers of inflammation. Patients and methods: We analysed sEPCR in 33 patients with CHI and 19 patients with PHI naive to ART. sEPCR was compared together with immunovirological parameters (HIV RNA and CD4 cell count) and IL-6 or D-dimer (DD). Results and conclusions: After 48 weeks of ART, in CHI, the sEPCR decrease was significant ( P  = 0.0006) and sEPCR at baseline was correlated with both CD4 cell increase ( r  = +0.463, P  = 0.007) and HIV RNA decrease ( r  = −0.363, P  = 0.038). In PHI, sEPCR was stable ( P  = 0.35); there was a correlation between 48 week DD change and IL-6 change ( r  = +0.696, P  = 0.0009) and also between 48 week DD change and sEPCR change ( r  = +0.553, P  = 0.014). Despite the small sample size, we hypothesize that sEPCR levels reflect coagulant pathway activation caused by the endothelial damage during chronic infection more than a marker of the cytokine storm that occurs during PHI. Alternatively, in PHI, the link found between sEPCR and DD secondary to IL-6 suggests sEPCR is an indirect marker of inflammation.